Beschichtung von gasgetragenen Nanopartikeln mit SiO2 mithilfe eines plasma‐unterstützten CVD‐Prozesses bei Umgebungsbedingungen. Issue 4 (13th February 2018) - Post, Patrick; Weber, Alfred P.
Abstract: A plasma‐assisted aerosol process is presented, which allows the continuous coating of particles with silicon oxide at ambient temperature. A dielectric barrier discharge plasma is applied to produce different reactive species. Tetraethyl orthosilicate is used as precursor. No elevated temperatures are necessary to perform the coating so that even temperature‐sensitive materials can be coated. Another advantage is the independence of the process from the particle source. The successful coating is demonstrated on different particle geometries and materials such as metals, salts and polymers and the dependence of the coating thickness on the particle surface area is shown. Furthermore, the change in particle number concentration along the coating reactor is primarily caused by agglomeration.